ROLE OF ULTRASOUND AND MAMMOGRAPHY FOR EVALUATION OF BREAST MASSES: A COMPARATIVE OBSERVATIONAL STUDY - RITIKA NIHAL,; RAMESH KUMAR SAHU,; HARI OM CHANDRAKAR, (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The aim of the study was to evaluate the diagnostic accuracy of ultrasound and mammography in the assessment of breast masses. Methods: This was a comparative observational study conducted in the department of radiology of a tertiary care medical institute. Fifty women coming for imaging of breast lumps were included in this study after applying inclusion and exclusion criteria. The demographic data, including age, sex, family history of breast cancer, personal history of breast disease, and other relevant clinical details, were collected for each patient to understand the population’s characteristics and ensure a comprehensive analysis. All patients underwent diagnostic mammography followed by sonography of the breast. Histopathological examination was done in 16 cases. Correlation between ultrasound features, mammography, and histopathological findings was done. p<0.05 was taken as statistically significant. Results: The mean age of the patients was found to be 40.2±9.6 years. Twenty-three cases (28.75%) presented with only a lump. In addition, 15 cases (18.75%) reported experiencing pain along with the lump. There were 5 cases (6.25%) that had a lump accompanied by discharge, while 7 cases (8.75%) showed skin changes in addition to the lump. Nipple retraction was observed in 6 cases (7.50%). Among benign lesions, fibroadenoma was the most common and in the malignant category, invasive ductal carcinoma was the most prevalent, found in 7 patients (14%). Ductal carcinoma in situ was present in 5 patients (10%), invasive lobular carcinoma in 2 patients (4%), and triple-negative breast cancer in 1 patient (2%). On USG, 35 cases were having benign (70%) and 15 (30%) cases were having malignant pathologies. Mammography detected 34 benign (68%) and 16 malignant (32%) cases. When a combination of USG and mammography was used, 21 (42%) pathologies were having malignant pathologies. Conclusion: Combined ultrasound and mammographic evaluation of breast lump was more helpful in the accurate evaluation of breast pathologies than when either modality was used alone.